2008
DOI: 10.5914/tropocean.v36i1-2.5085
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the mesozooplankton at continental shelf off Sergipe, Brazil

Abstract: The purpose of this work was to study the composition and abundance of the mesozooplankton at two stations at the continental shelf off Sergipe. At each station, oblique plankton tows were carried using plankton nets with 200 µm mesh size, in six hours intervals during three consecutive days. One hundred and three taxa were identified and Copepoda was the dominant group with fifty one species. The mesozooplankton assemblage was composed by coastal, neritic and oceanic tropical species. There were significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
3
1
0
Order By: Relevance
“…[32] and [33] point out that copepods are the most abundant group of multicellular metazoan zooplankton in the oceans and even on Earth. The dominance of copepods in the zooplanktonic population of the Kribian coast obtained in this study is in line with the results observed in the bibliographic synthesis on the zooplankton of the neritic waters of the Atlantic Ocean on the coasts of Côte d'Ivoire (58%) [28], Brazil (approximately 50%) [29], the Atlantic coasts of Morocco (73%) [30] and Senegal (27 to 93%) [34]. The spatio-temporal distribution of abundance showed an overall abundance of copepods in all stations and during all months with a predominance of the families Paracalanidae, Oithonidae and Euterpinidae.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[32] and [33] point out that copepods are the most abundant group of multicellular metazoan zooplankton in the oceans and even on Earth. The dominance of copepods in the zooplanktonic population of the Kribian coast obtained in this study is in line with the results observed in the bibliographic synthesis on the zooplankton of the neritic waters of the Atlantic Ocean on the coasts of Côte d'Ivoire (58%) [28], Brazil (approximately 50%) [29], the Atlantic coasts of Morocco (73%) [30] and Senegal (27 to 93%) [34]. The spatio-temporal distribution of abundance showed an overall abundance of copepods in all stations and during all months with a predominance of the families Paracalanidae, Oithonidae and Euterpinidae.…”
Section: Discussionsupporting
confidence: 91%
“…The spatio-temporal distribution of abundance showed an overall abundance of copepods in all stations and during all months with a predominance of the families Paracalanidae, Oithonidae and Euterpinidae. These observations partially corroborate those made on the Brazilian continental shelves in the State of Sergipe and in Ivory Coast where ( [29] and [28] respectively observed the predominance of the family Paracalinidae in their work.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This large number of Copepoda recorded in the CSM is similar to that in other tropical regions of Brazil. Araujo and Ribeiro (2008) 2010) say that large, medium, and small crustacean copepods are the main food resources for fish, while carnivorous individuals (such as gelatinous individuals) compete with other organisms to obtain food, and their energy may not be efficiently transferred to higher trophic levels.…”
Section: Discussionmentioning
confidence: 99%